PHARMACEUTICAL STANDARDIZATION OF PANCHAGUNA TAILA (MEDICATED OIL) AND PRODUCT DEVELOPMENT AS OINTMENT, GEL, CREAM, AND PHYSIOWAX - Kumari, Sweta; Baghel, Dileep Singh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The present study aimed to prepare Panchaguna taila (PGT) and its development in various dosage forms, i.e. ointment, gel, cream, and physiowax to exemplify the characteristic parameters according to pharmaceutical standards. Methods: PGT is polyherbal medicated oil used externally for treating wounds, cut, and burn and used for massaging in rheumatoid arthritis, muscular pain, sprains, and joints pain. Prepare the decoction using Haritaki, Vibhitaki, Amalaki, Nimba, Sambhalu and prepare paste (kalka) from Madhuchishta, Gandhaphiroja, Shilarasa, Rala, and Guggulu. Mix all the ingredients and heat till watery portion not evaporated from the oil with constant stirring then filter it. Add eucalyptus oil, turpentine oil, and kejoputi oil at the end and stir it well. Prepare various dosage forms like ointment, gel, cream, and physiowax using suitable base for the better and improved therapeutic application. Analytical standards for PGT such as acid value, saponification value, iodine value, and peroxide value were performed, and obtained results were appeared under the prescribed limit of the official monograph. Various physicochemical parameters such as homogeneity, spreadability, pH, and melting point were performed for PGT ointment, PGT gel, PGT cream, and PGT physiowax. Stability study of PGT was done for 3 days under the accelerated conditions. Results: In PGT, various physicochemical parameters were performed on the interval of 24, 48, and 72 hrs, and no significant variation found in their physicochemical properties when observed values were compared. PGT ointment, PGT gel, PGT cream, and PGT physiowax containing PGT as active pharmaceutical ingredient with various suitable excipients and base are easy to formulate and convenient to apply over the affected area. Rf observed between the ranges 0.21 to 0.84 as given in the standard monograph. In PGT, PGT ointment and PGT physiowax, 10 spots were found, and in PGT gel and PGT cream, 7 spots were found. 0.11, 0.15, and 0.34 spots were found in the PGT gel, PGT cream, and PGT physiowax, respectively, that can be given by the excipients or base used for their preparation. Conclusion: It is possible to make other dosage form of PGT which can be more convenient to the customers. Hence, the issues related to the PGT like staining and sticking can be resolved by developing or converting the PGT into various convenient dosages.